2019
DOI: 10.1111/hepr.13342
|View full text |Cite
|
Sign up to set email alerts
|

Increase trend in the prevalence and male‐to‐female ratio of primary biliary cholangitis, autoimmune hepatitis, and primary sclerosing cholangitis in Japan

Abstract: Aim Autoimmune liver diseases (AILD) including autoimmune hepatitis (AIH), primary biliary cholangitis (PBC), and primary sclerosing cholangitis (PSC) impose a significant burden on public health, and it is important to estimate their prevalence. We carried out a nationwide, hospital‐based, epidemiological survey of AIH, PBC, and PSC, and compared the results with those from previous surveys. Method We randomly selected health‐care facilities used in the survey from a list of all facilities in Japan. The selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 57 publications
8
71
0
Order By: Relevance
“…Among the 11 studies with moderate quality, seven studies were attributed to insufficient case‐finding strategies, such as including only a single hospital data or only outpatients, or only children, while the other four studies were due to the imperfect case‐ascertainment process performed by other diagnostic criteria . Three studies were regarded as poor quality because the case‐ascertainment process was not reported …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 11 studies with moderate quality, seven studies were attributed to insufficient case‐finding strategies, such as including only a single hospital data or only outpatients, or only children, while the other four studies were due to the imperfect case‐ascertainment process performed by other diagnostic criteria . Three studies were regarded as poor quality because the case‐ascertainment process was not reported …”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28] Sixteen studies reporting AIH prevalence rates were included, with nine from Europe, 6,7,9,11,12,20,21,23,24 two from America, 4,29 and five from Asia. 3,5,8,10,30 The characteristics of these studies are summarized in Table 2. In addition, five eligible studies were available to calculate the genderspecific incidence 5,11,23,26,27 and 10 for gender-specific prevalence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations